Use of a Sensing Device to Visualizes Group Participation in Social Skills Learning Groups - Yamamoto, Tomoka; Okuno, Hiroko; Tatsumi, Aika; Sakai, Saeko; Mohri, Ikuko; Taniike, Masako (Frontiers in Psychiatry, 2021)
Children with autism spectrum disorders (ASD) have difficulties in developing stable peer relationships. Interventions for learning social skills (SS) for such children are often conducted in a group. Behavioral imaging and social imaging, which have been called for in recent years, are methods for visualizing children's behaviors and interpersonal relationships. To examine the usefulness of visualizing face-to-face interaction with others in the social skills learning scene of children with ASD, we use a business microscope that can qualify and visualize face-to-face interactions automatically. We highlight two boys’ face-to-face interaction changes in the same SS learning group of five children. The device's use may provide a more objective measurement that complements the observer's subjective evaluation in case of the intervention's validation. It is expected that information on face-to-face interactions will be used to determine the SS learning process in the future.